The Dynamics of Lampung Pepper Trade Network in 16th - 18th Century - Hamid, Abd Rahman (Buletin Al-Turas, 2024)
PurposeThe purpose of this study was to analyze the dynamics of Lampung's pepper trade in regional and international networks in the 16th to 18th centuries with three focuses: Lampung's position in the Nusantara shipping routes, the pepper production system in Lampung, and Lampung's pepper trade network. MethodThis study used the historical method, which consists of four stages: heuristics (collecting historical sources), external and internal source criticism, interpretation, and historiography (writing history). The data sources used were local and foreign sources to explain the focus of the study. Results/FindingsThe results found that Lampung had an important role in developing the maritime trade network due to its strategic location on the Nusantara shipping route, especially after the Portuguese controlled the port of Malacca in 1511. Following this situation, Banten became a major international pepper port city in the Sunda Strait. The primary source of pepper was from Lampung. This activity formed four trade networks between Lampung and Banten, Palembang, Batavia (Netherlands) and Bengkulu (UK). Before the second half of the 17th century, the network was stronger with Banten and Palembang, but afterward, it shifted under the influence of Batavia and Bengkulu. All parties used all possible ways to get the Lampung pepper.   ConclusionThis study shows that Lampung pepper was a significant factor driving Lampung's history and contribution to regional and international trade networks over two centuries.